The influence of resonant leadership on teachers' innovative behavior: The mediating mechanism of information processing models. - Yuangen Bao (PLoS ONE)
Teacher innovation is crucial for adapting education to contemporary societal needs. While the benefits of resonant leadership have been extensively studied, its influence on teachers' innovative behavior and associated cognitive-affective processes remains underexplored. This study employs the information processing theory to investigate the influence of resonant leadership on innovative behavior among primary and junior teachers in mainland China, while examining the intricate mediating roles of perceived insider status and affective commitment. Using structural equation modeling and bootstrapping techniques, data analysis was conducted on a sample comprising 4,769 teachers from 16 provinces in China. The findings confirm a positive correlation between resonant leadership and teachers' innovative behavior. Perceived insider status and affective commitment not only independently mediate this relationship but also act as sequential and interactive mediators. Furthermore, the distinct mediating effect of interactive mediation is the most important. This research enhances our understanding of resonant leadership's impact on basic education while providing novel insights into fostering teacher innovation through comprehensive cognitive-affective pathway analysis.